PENGIMPLEMENTASIAN PERATURAN BUPATI PADA SATUAN PENDIDIKAN FORMAL DAN NON-FORMAL, EFEKTIFKAH? - Dewi Ambarwati; Assiddiq, Dafis Ubaidillah (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2024)
This study aims to: determine the implementation of Regent Regulation No. 29 of 2020 concerning PPK and PAK in Formal and Non-Formal Education Units at the Elementary Education, Child Education and Equality Education levels, especially in Balesari Village. In addition, to find out the obstacles and solutions carried out by the Village Government related to the policy. This research is anempirical juridical research. The data collection techniques carried out by the researcher are by conducting observations, interviews and documentation. Meanwhile, data processing techniques are carried out by means of data examination (editing), data classification (classifying), verification (Verifying), analysis (Anlysis) and Conclusions (Conclusion))(Muhaimin, 2020). The results of this study found that Balesari Village has made efforts to strengthen character education and anti-corruption by synergizing with education activists, anti-corruption activists, universities and from non-formal educators. The obstacles experienced are related to the skills needed when conducting anti-corruption education for students and the lack of public knowledge related to anti-corruption.